The Multifaceted Value of Post-Classroom Questionnaires in Master Medical Education Programs: From Reflection to Continuous Improvement - Hermanto TJ (Asian Journal of Health Research, 2026)
Introduction: Post-classroom questionnaires (PCQ) in graduate medical education may serve as more than satisfaction surveys; when grounded in educational theory and analyzed semiquantitatively, they can be interpreted as tools for reflective practice, Continuous Quality Improvement (CQI), and Outcome-Based Education (OBE). Material and Methods: This study employed a descriptive semiquantitative program evaluation design within a Master Medical Education Program, analyzing routinely collected, anonymized learner feedback across multiple classroom sessions. Items addressed domains including program identity, onboarding, pedagogy, assessment, institutional support, and perceived value. Results: A 51% response rate yielded patterns of consistently high endorsement for program mission, orientation, student-centered learning, and assessment-as-learning, while flipped classroom implementation, holistic competency development, and research/publication support received comparatively lower ratings. Institutional support was positively perceived, though tuition value was rated less favorably. These contrasts may suggest interpretive hypotheses of systemic misalignment, such as a potential resource–expectation gap in scholarly mentorship, or a pedagogical implementation trap in innovative teaching strategies. By emphasizing pattern recognition and relative contrasts rather than inferential claims, this evaluation generates hypotheses that warrant further exploration and can inform curricular refinement, faculty development, and policy adjustment. Conclusion: Post-classroom questionnaires, when systematically embedded within CQI–OBE frameworks, may thus function as low-burden, high-impact instruments that foster reflective professionalism, evidence-informed decision-making, and sustainable excellence in postgraduate medical education.